PERBEDAAN HASIL BELAJAR PESERTA DIDIK YANG MENGGUNAKAN MODEL PEMBELAJARAN ACTIVE LEARNING TIPE COURSE REVIEW HORAY DENGAN TIPE THINK PAIR SHARE - Yayat Hidayat (Faculty of Teacher Training and Education, 2020)
This research is motivated by the fact that in Class VIII SMP Plus Ma'arif NU Pangandaran that Learning is still teacher centered, lack of student involvement during the learning process, students generally act passively and are afraid or embarrassed to ask questions when experiencing difficulties in learning, not optimal use of the active method learning type course review horay, and not yet optimal use of active learning methods think pairs share type. The purpose of this study was to study, find out, and analyze: (1) Improvement of student learning outcomes (Pretest and Posttest) using the active learning model type course review horay in Islamic Religious Education Class VIII Middle School Plus Ma'arif NU Pangandaran. (2) Improving student learning outcomes (Pretest and Posttest) by using active learning learning models think pair share type in Islamic Religious Education Subjects Class VIII SMP Plus Ma'arif NU Pangandaran. (3) Differences in student learning outcomes by using the active learning model review course type horay with the type of think pair share in Islamic Religious Education Subjects Class VIII SMP Plus Ma'arif NU Pangandaran. The research method used is experiment.